Long Non-Coding RNA LINC01123 Facilitates Cholangiocarcinoma Aggravation by Targeting miR-641 - Wu, Xueshuo; Wang, Ling; Wang, Xiaoming; Kuang, Deli; Yuan, Chunmiao; Xiao, Kun (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Cholangiocarcinoma (CCA) is a malignant and insidious tumor that is tricky to treat. Long non-coding RNA (LncRNA) LINC01123 is a biomolecule that influences cancer progression by regulating gene expression via influencing the regulatory function of microRNAs in gene expression. Therefore, this study investigated the connection between LINC01123 and CCA and explored the under lying mechanism. The objective of this study was to provide valuable information on the management of CCA. Materials and Methods: Tumor and normal paracancer tissue samples in this study were collected from 128 CCA patients. To measure LINC01123 and miR-641 expression characteristics, quantitative reverse transcription-polymerase chain reaction was used. To explore the biological functions of LINC01123 and miR-641 in CCA cells, cell counting Kit-8 (CCK-8) and transwell migration and invasion assays were used. The mechanism was investigated using dual luciferase reporter assays and rescue experiments. Results: This study found that the expression levels of LINC01123 were higher in CCA tissues and cells than in normal tissues and cells. LINC01123 promoted the proliferation, migration and invasion ability of CCA cells and consequently became an indicator of lymph node metastasis and advanced TNM stage in CCA. Moreover, the expression of miR-641 was negatively correlated with the expression of LINC01123. LINC01123 affected CCA progression by downregulating miR-641. Conclusion: There was an upregulation of LINC01123 in CCA tumor tissues and cells. LINC01123 promoted CCA aggravation by target ing miR-641. LINC01123 could be the target of future treatment for CCA. Cite this article as: Wu X, Wang L, Wang X, Kuang D, Yuan C, Xiao K. Long non-coding RNA LINC01123 facilitates cholangiocarcinoma aggravation by targeting miR-641. Turk J Gastroenterol. 2025;36(3):183-192.